Attack Resistant Agent Based Dynamic Key Management in Dynamic Wireless Sensor Networks - Shaik, Riaz; Shakeel Ahamad, Shaik (International Journal of Engineering and Technology, 2018)
The adaptation of Wireless Sensor Network (WSN) and its utility in real world applications like healthcare is growing faster. With its growth, it also brought vulnerabilities that cause security attacks. It is more so with the emerging technology known as Internet of Things (IoT) which combines physical and digital worlds. At least, as far as WSN is concerned, it is inevitable to have end to end security to protect communications that are sensitive and confidential.Many security schemes came into existence as found in the literature. However, most of them are inefficient for dynamic key management in dynamic WSN. Recently we proposed a scheme named as Agent Based Dynamic Key Management (ABDKM). In this paper we enhance and evaluate it against various attacks such as black hole and rushing.The enhanced scheme is named as an Attack Resilient-Agent Based Dynamic Key Management (AR-ABDKM). The scheme is implemented using NS2. The simulation results showed the remarkable performance improvement of the proposed scheme besides its attack resiliency.Â Â